Early human dispersals within the Americas - Moreno-Mayar, J. Victor; Vinner, Lasse; Damgaard, Peter de Barros; de la Fuente, Constanza; Chan, Jeffrey; Spence, Jeffrey P.; Allentoft, Morten E.; Vimala, Tharsika; Racimo, Fernando; Pinotti, Thomaz; Rasmussen, Simon; Margaryan, Ashot; et al. (My University, 2018)
Studies of the peopling of the Americas have focused on the timing and number of initial migrations. Less attention has been paid to the subsequent spread of people within the Americas. We sequenced 15 ancient human genomes spanning from Alaska to Patagonia; six are >= 10,000 years old (up to similar to 18x coverage). All are most closely related to Native Americans, including those from an Ancient Beringian individual and two morphologically distinct "Paleoamericans." We found evidence of rapid dispersal and early diversification that included previously unknown groups as people moved south. This resulted in multiple independent, geographically uneven migrations, including one that provides clues of a Late Pleistocene Australasian genetic signal, as well as a later Mesoamerican-related expansion. These led to complex and dynamic population histories from North to South America.
Keywords: Human migration; Out of africa